Optimization of Career Guidance through Orientation Services to Enhance Career Understanding of 11th Grade Students - Wahyu Indah Sari; Yenti Arsini (Academia Open, 2025)
General Background: Education plays a vital role in developing human resources, and high school is a crucial stage where students must prepare for higher education or future careers. However, many students in Indonesia still struggle with unclear career goals and a lack of self-awareness. Specific Background: Existing career guidance programs in schools often remain underdeveloped due to limited resources and monotonous implementation. Knowledge Gap: Previous studies have highlighted the importance of career guidance but have rarely focused on optimizing orientation services as a specific strategy to improve students’ career understanding.Aim: This study aims to optimize career guidance through orientation services based on Holland’s RIASEC theory to enhance the career understanding of 11th-grade students. Results: Using a descriptive qualitative approach, findings revealed that orientation services improved students’ self-awareness, confidence, and career decision-making ability. Novelty: The study uniquely integrates the RIASEC model within school-based orientation services, offering a structured and reflective career development framework.Implications: The findings suggest that continuous orientation services starting from Grade X can effectively strengthen students’ career planning and provide practical insights for counselors in designing more targeted and sustainable career programs. Highlights: Enhances students’ self-awareness and confidence in career decision-making. Integrates Holland’s RIASEC model into structured school orientation programs. Recommends continuous career guidance starting from Grade X for sustainability. Keywords: Orientation Services, Career Understanding, Riasec Theory, Career Guidance, High School Students